2022
DOI: 10.1111/lam.13751
|View full text |Cite
|
Sign up to set email alerts
|

The denture microbiome in health and disease: an exploration of a unique community

Abstract: Dentures are becoming increasingly common. Since colonisation (and subsequence biofilm formation) by some microorganisms to dentures can significantly impact, the study of denture microbiology has long been of interest to researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 128 publications
(219 reference statements)
0
25
0
1
Order By: Relevance
“…As dentures are not sterile and are used at the body‐external environment interface, it is possible to be colonized by microorganisms. Once placed in the patient's mouth, the denture surface becomes coated with an 'acquired pellicle' of salivary glycoproteins (including salivary amylase, albumin, mucin, and lysozyme) and immunoglobulins [ 19 ]. The prosthesis surfaces represent the interface being colonized by oral biofilm a few hours after placement [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As dentures are not sterile and are used at the body‐external environment interface, it is possible to be colonized by microorganisms. Once placed in the patient's mouth, the denture surface becomes coated with an 'acquired pellicle' of salivary glycoproteins (including salivary amylase, albumin, mucin, and lysozyme) and immunoglobulins [ 19 ]. The prosthesis surfaces represent the interface being colonized by oral biofilm a few hours after placement [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…On a more positive note over recent years there has been a steady decline in the proportion of the population who have no natural teeth. Nevertheless, this will not immediately translate into a reduction in denture wearing [ 32 ]. A recent survey of adults attending dental practices in the UK reported that 13.7% had partial dentures; with a higher prevalence with increasing age so that more than 40% of those aged 75 or over were partial denture wearers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of adults attending dental practices in the UK reported that 13.7% had partial dentures; with a higher prevalence with increasing age so that more than 40% of those aged 75 or over were partial denture wearers [ 33 ]. Our understanding of the long-term consequences of complete and partial denture use is limited, particularly in relation any possible associations with systemic diseases or conditions [ 32 , 34 ]. If, as suggested by the results of the present study, denture wearing in individuals who retain at least some of their natural teeth, could increase the risk of poorer lung function, then it will be important to assess the implications at a public health level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations